Deep sea mining's future effects on Fiji's tourism industry: A contingent behaviour study. (October 2018) - Folkersen, Maja Vinde; Fleming, Christopher M.; Hasan, Syezlin
Abstract: Pristine coral reefs possess a tremendous potential for contributing to tourism and economic development. This is especially important for Fiji given their tourism economy's reliance on diving and coastal activities. Understanding divers' perceptions of coral reefs and environmental issues is, therefore, paramount to sustaining the tourism industry. Despite the importance of coral reefs to the Fijian tourism sector, the Fijian Government has granted exploration licenses to mining companies to assess the viability of deep sea mining (DSM) activities in Fiji's seas. There is concern that DSM may negatively impact reef-related tourism due to tourists' perception that DSM activities degrades Fiji's coral reefs. This study conducts a contingent behaviour survey to explore how tourists' expectations of DSM will affect their future travel decisions and subsequently influence overall tourism demand in Fiji. Our findings show that divers and snorkelers demonstrate a high willingness to return to Fiji in the future, based on their previous travel experience, but that they would significantly reduce their future visits if DSM was to take place in Fiji. These results contribute to our understanding of the potential trade-offs between DSM and reef-related tourism and give some preliminary estimates of the potential economic consequences of the Fijian Government allowing DSM within their territorial waters. Highlights: Diving industry is important for Fiji's tourism economy. Deep sea mining exploration licenses have been granted for Fiji's seas. Deep sea mining's environmental impacts on marine systems are uncertain. This study indicates that divers' perception of deep sea mining could severely impact Fiji's tourism economy. Caution required when forming deep sea mining policy.